2011
DOI: 10.1371/journal.pgen.1001302
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Adaptive Protein Evolution Apparent in Diversity Patterns around Amino Acid Substitutions in Drosophila simulans

Abstract: In Drosophila, multiple lines of evidence converge in suggesting that beneficial substitutions to the genome may be common. All suffer from confounding factors, however, such that the interpretation of the evidence—in particular, conclusions about the rate and strength of beneficial substitutions—remains tentative. Here, we use genome-wide polymorphism data in D. simulans and sequenced genomes of its close relatives to construct a readily interpretable characterization of the effects of positive selection: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
162
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(173 citation statements)
references
References 45 publications
10
162
1
Order By: Relevance
“…Other, more sophisticated, extensions try to infer the actual DFE at functional sites from the SFS, based on the assumption of the mutation-selection-drift balance (SI Text). It is well known that genetic draft and background selection can distort the SFS from this expectation (6,10,(34)(35)(36)(37)(38)(39). What is not clear is whether the deviations are substantial under realistic evolutionary scenarios and whether this might affect methods based on the assumption of mutation-selection-drift balance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other, more sophisticated, extensions try to infer the actual DFE at functional sites from the SFS, based on the assumption of the mutation-selection-drift balance (SI Text). It is well known that genetic draft and background selection can distort the SFS from this expectation (6,10,(34)(35)(36)(37)(38)(39). What is not clear is whether the deviations are substantial under realistic evolutionary scenarios and whether this might affect methods based on the assumption of mutation-selection-drift balance.…”
Section: Resultsmentioning
confidence: 99%
“…First, in many species the rate of adaptation appears to be very high with, for example, in Drosophila melanogaster more than 50% of the amino acid changing substitutions, and similarly large proportions of noncoding substitutions, driven to fixation by positive selection (3). Importantly, it appears that frequent adaptation strongly affects the genome-wide patterns of polymorphism (3)(4)(5)(6). These results imply that the dynamics of a given polymorphism is not only affected by genetic drift and purifying selection acting at its particular site, but also by the socalled genetic draft (7), which describes the stochastic effects generated by recurrent selective sweeps at closely linked sites.…”
mentioning
confidence: 99%
“…Eyre-Walker (2006) assumed that the correlation between nucleotide diversity and recombination rate was due to selective sweeps, whereas Macpherson et al (2007) inferred the strength of selection from an analysis of genome-wide heterogeneity in diversity levels in Drosophila. Recently, Sattath et al (2011) suggested that these conflicting results can be resolved. By analyzing the pattern of diversity around synonymous and nonsynonymous substitutions, they inferred that two classes of effects of adaptive mutations, with effects of $0.5% and $0.01%, best explain polymorphism and divergence data in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…In several recent analyses p a and N e s a have been estimated separately by several different methods, using polymorphism and divergence data sets from Drosophila. Very disparate estimates have been obtained by these methods, ranging from a very low frequency of adaptively favorable mutations with relatively strong selective advantages (Eyre-Walker 2006;Li and Stephan 2006;Macpherson et al 2007;Jensen et al 2008;Jensen 2009) to a relatively high frequency with a very small mean selective advantage (Sawyer et al 2003;Andolfatto 2007) and a mixture of strongly and weakly selected advantageous mutations (Sattath et al 2011).…”
mentioning
confidence: 99%
“…As neutral diversity levels slowly recover through an influx of new mutations after the sweep, there is a strong skew toward low-frequency derived alleles, a pattern that persists for many generations (Braverman et al 1995;Przeworski 2002;Kim 2006). In a large population, the rate of sweeps could be high enough that hitchhiking dominates genetic drift as the source of stochasticity (Maynard Smith and Haigh 1974;Kaplan et al 1989;Gillespie 2000), an idea that has been termed genetic draft (Gillespie 2000).Support for a hitchhiking model over the standard model of background selection is found in Drosophila, where there is a greater skew toward rare alleles at putatively neutral sites in regions of low recombination (Andolfatto and Przeworski 2001;Shapiro et al 2007) and regions surrounding amino acid substitutions have lower levels of diversity (Andolfatto 2007;Macpherson et al 2007;Sattath et al 2011). However, in humans (and other species) there is no strong skew toward rare alleles in low-recombination regions (McVicker et al 2009;Hernandez et al 2011;Lohmueller et al 2011), which combined with other evidence (Coop et al 2009;Hernandez et al 2011) suggests that full sweeps may have been rare and that background selection may be the main mode of linked selection, in humans and a number of other species.…”
mentioning
confidence: 99%